Food-derived cyanidin-3-O-glucoside alleviates oxidative stress: evidence from the islet cell line and diabetic db/db mice. Issue 22 (29th October 2021) - Ye, Xiang; Chen, Wen; Tu, Pengcheng; Jia, Ruoyi; Liu, Yangyang; Li, Yonglu; Tang, Qiong; Zheng, Xiaodong; Chu, Qiang
Abstract : C3G can effectively relieve cellular oxidative stress induced by HG and PA. The antioxidant effect of C3G was achieved by activating mitophagy via the PINK1-PARKIN signaling pathway. Abstract : Type 2 diabetes mellitus is a disease associated with an oxidative milieu that often leads to adverse health outcomes. Multiple anthocyanins have been reported to possess outstanding antioxidant activity, however, their effects on hyperglycemia-related oxidative stress remain elusive. In the present study, cyanidin-3- O -glucoside (C3G), a typical anthocyanin with various widely accepted health benefits, was applied to alleviate oxidative stress in pancreas islets under the conditions of hyperglycemia. Firstly, significantly decreased mitochondrial membrane potential (MMP) and antioxidant enzymes, as well as increased reactive oxygen species (ROS) and O2 − levels, were detected after exposure to a series of concentrations of high glucose (HG) and palmitic acid (PA), which manifested oxidative stress triggered by mitochondrial damage. To evaluate the antioxidant effect of C3G in vitro, the islet cell line NIT-1 was used, and results proved that C3G could effectively relieve cellular oxidative stress induced by HG and PA. Furthermore, we found that the antioxidant effect of C3G was achieved by activating mitophagy via the PINK1-PARKIN signaling pathway. More importantly, an autophagy inhibitor chloroquine (CQ) was added to verify our findings at the protein level, and we observed the co-localization of mitochondria and lysosomes, which may form autophagolysosomes to clean damaged mitochondria. Immediately afterwards, more studies were conducted on pancreatic islets of diabetic db/db mice to verify the antioxidant effect of C3G discovered in islet cells. Along with the decline in fasting blood glucose, the oxidative stress in pancreas islets was successfully alleviated in diabetic db/db mice after supplementation with C3G. This was demonstrated by increased levels of ROS, and the impaired activities of anti-oxidative enzymes superoxide dismutase (SOD) and catalase (CAT) were partly reversed by C3G intervention. Our study has provided evidence for the alleviation effect of C3G against oxidative stress in pancreas islets, which may provide enlightenment for improving the health situation of diabetic patients in the future.